Climate Change as a Human Rights Issue: Legal Accountability and State Obligations in Protecting Vulnerable Communities - Friget Wiyanto; Hardiman Hardiman; Rania Khatib (Rechtsnormen: Journal of Law, 2026)
Background. Climate change disproportionately affects vulnerable communities in developing nations, threatening fundamental rights to life, health, and resources. While recognized as a human rights issue, current legal frameworks often fail to ensure state accountability for protecting these groups. Purpose. The study investigates the relationship between climate change and human rights law to explore how international and national legal structures can be strengthened to enforce state obligations toward affected populations. Method. A qualitative research design was utilized, consisting of a legal analysis of international treaties, conventions, and case law, complemented by interviews with human rights experts and climate practitioners. Results. The findings identify significant gaps in legal accountability, noting that many international agreements lack the enforceable provisions necessary to provide concrete protection for vulnerable populations. Conclusion. The research concludes that effective protection requires stronger, binding legal frameworks with clearly defined state obligations. Legal reforms are essential to transform climate change discourse into actionable human rights protection.